Pediatric cerebral stroke induced by Epstein-Barr virus infection: Role of Interelukin overexpression - Gatto, Antonio; Angelici, Serenella; Soligo, Marzia; Di Giuda, Daniela; Manni, Luigi; Curatola, Antonietta; Ferretti, Serena; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Introduction: Ischemic stroke is an important cause of death and long-term morbidity in children. Viral respiratory infections are emerging as important risk factors for ischemic stroke in this age group of patients. Direct action of virus against cerebral vessels, autoimmune reactivity, and an increased production of cytokines have all been advocated as main factors in determining ischemic stroke. Case report: We report the case of an EBV-induced ischemic stroke in a caucasian 2 year-old female. The cerebrospinal fluid samples showed positivity of polymerase chain reaction for EBV infection, also confirmed by pharyngeal swab culture. Increased levels of interleukin 6 and interleukin 1b were also detected in the cerebrospinal fluid. Discussion: EBV infection has been identified as an important cause of neurological involvement in children. Findings of increased levels of interleukin 6 and interleukin 1b in the cerebrospinal fluid of the child with EBV induced-ischemic stroke seems to validate the role of pro-inflammatory cytokines as crucial mediators of cerebral thrombus formation. Conclusions: We believe that this report can be useful to clarify some pathophysiological mechanisms related to ischemic stroke related to Epstein-Barr Virus (EBV) infection in children.